Design of 70% PAE Class‐F 1.2–1.4 GHz 10 W GaN power amplifier MMIC. Issue 4 (8th February 2022) - Zhang, Lu‐Chuan; Shi, Long‐Xing
Abstract: This letter presents a novel design of a Class‐F monolithic microwave integrated circuit (MMIC) power amplifier (PA) operating at L‐band with a power‐added‐efficiency (PAE) better than 70%. The MMIC PA is designed via load/source‐pull techniques to locate the optimal impedances at fundamental and harmonic frequencies on not only output but also input terminations. Moreover, rather than quarter wavelength stubs used in conventional designs, several parallel/series LC resonators are utilized to behave open/short at certain harmonics and to reform the drain waveform, yielding highly efficient performance of the PA MMIC. A prototype PA MMIC validating the proposed method is designed, fabricated and measured, which implemented on a 0.25 μm gallium nitride high electron mobility transistor technology. The measurement results of the PA under a drain voltage of 28 V at 1 ms pulse width with 30% duty cycle demonstrated a PAE better than 70% over 1.2–1.4 GHz with an output power greater than 40 dBm (10 W). The chip size is 2.5 mm × 3.5 mm (8.75 mm 2 ).